2022
DOI: 10.1111/jocd.15085
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the quality of life of cosmetic users: A cross‐sectional analysis from eight Arab countries in the Middle East

Abstract: Background: The use of cosmetic products is growing in dominance in the Arab population, making it essential to measure its effects on users. The production of cosmetics has been largely driven by consumerism and a bid to keep abreast with the latest trends in the beauty industry with less attention on how the users' quality of life (QoL) is affected.Aims: This study aims to investigate the effect of cosmetic products on users' quality of life in eight Arab countries. Methods:A cross-sectional study was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…This comprised the largest beauty shoppers among makeup stalls. Similarly, study had found that majority of the cosmetics users are those who attained tertiary level of education [13] . This suggests that the consumers of makeup were individuals who reached bachelor's degree.…”
Section: Resultsmentioning
confidence: 91%
“…This comprised the largest beauty shoppers among makeup stalls. Similarly, study had found that majority of the cosmetics users are those who attained tertiary level of education [13] . This suggests that the consumers of makeup were individuals who reached bachelor's degree.…”
Section: Resultsmentioning
confidence: 91%
“…In this context, in 2012 the BeautyQoL was designed to assess the impact of cosmetic products on quality of life [49,51] and was already used to evaluate the impact of cosmetics in specific groups (e.g. cosmetic consumer in the Middle East [52]). Additional published studies evaluating single cosmetic products using this instrument are to our knowledge not available up to now, especially in terms of skin cleansing.…”
Section: Evaluation Of the Impact On Mood-and Well-beingmentioning
confidence: 99%
“…There was evidence that women performed better in the recognition of minor modifications in facial skin than men ( Samson et al, 2010b ). This difference may be explained by the fact that the main consumers of cosmetic and facial beauty treatments are women ( Jin et al, 2022 ; Mohammed et al, 2022 ), making them to be more sensitive to facial skin conditions. Male and female judgments of male and female faces were mostly consistent in this study.…”
Section: Experiments 2: Perceiving Facial Attractiveness Changementioning
confidence: 99%